TURISLO: Exploring the Role of Trust and Risk Perception in Driving Generation Z Loyalty Through Customer Satisfaction in Tiktokshop - Elia Resha Fatmawati (STIE Amkop Makassar, 2026)
This study aims to analyze the influence of Customer Trust and Risk Perception on Customer Loyalty, with Customer Satisfaction as a mediating variable among Generation Z users of TikTok Shop in Semarang City. This quantitative study involved 100 respondents. The results indicate that Customer Trust has a positive and significant effect on Customer Satisfaction as well as Customer Loyalty. In contrast, Risk Perception does not have a significant effect on Customer Satisfaction, but it has a positive and significant effect on Customer Loyalty. Customer Satisfaction is also proven to have a positive and significant effect on Customer Loyalty. The mediation test shows that Customer Satisfaction does not mediate the effect of Customer Trust on Customer Loyalty, indicating that trust can directly shape loyalty. However, Customer Satisfaction is able to mediate the effect of Risk Perception on Customer Loyalty, meaning that perceived risk increases satisfaction and ultimately encourages loyalty. These findings confirm that trust is the primary factor in shaping Generation Z loyalty, while effective risk management strengthens loyalty through increased customer satisfaction.